Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2021)
A dataset containing 109861 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is one of (Hildbrandetia Özdikmen, 2005, Hildebrandtia Nieden, 1907, Hildebrandtia Vatke, Hildebrandtia Nardo, Hildebrandtia Olsoufieff, 1938, Hildbrandtia Nardo, 1834, Hildebrandia, Hildebrandia Jordan & Evermann, 1927, Hildebrandtina Weise, 1910, Hildenbrandia Nardo, 1834, Hillebrandia Oliv., Hildbrandetia Özdikmen, 2005, Hildebrandtia Nieden, 1907, Hildebrandtia Vatke, Hildebrandtia Nardo, Hildebrandtia Olsoufieff, 1938, Hildbrandtia Nardo, 1834, Hildebrandia, Hildebrandia Jordan & Evermann, 1927, Hildebrandtina Weise, 1910, Hildenbrandia Nardo, 1834, Hillebrandia Oliv., Hildbrandetia Özdikmen, 2005, Hoplobatrachus Peters, 1863, Hoplobactrachus Theobald, 1868, Halobatrachus Ogilby, 1908, Hylobatrachus Laurent, 1943, Halobatrachus Hammer, 1987, Hoplobatrachus Peters, 1863, Hoplobactrachus Theobald, 1868, Halobatrachus Ogilby, 1908, Hylobatrachus Laurent, 1943, Halobatrachus Hammer, 1987, Hoplobatrachus Peters, 1863, Hoplobactrachus Theobald, 1868, Halobatrachus Ogilby, 1908, Hylobatrachus Laurent, 1943, Halobatrachus Hammer, 1987, Hoplobatrachus Peters, 1863, Hoplobactrachus Theobald, 1868, Halobatrachus Ogilby, 1908, Hylobatrachus Laurent, 1943, Halobatrachus Hammer, 1987, Huia Yang, 1991, Huia B.-Y.Geng, 1985, Huia H.F.Gu, K.N.Mertens & T.T.Liu, 2016, Heia Chen & van Achterberg, 1997, Hoia Avdeev & Kazachenko, 1986, Huea, Huka Forster & Wilton, 1973, Hura L., Hura J.Koenig, Hoia Schallreuter, 1986, Huea C.W.Dodge & G.E.Baker, 1938, Houia Selden et al., 2015, Hsuia Ferris, 1950, Hua Pierre ex De Wild., Hua S.-F.Chen, 1943, Hua Distant, 1906, Hugia Buckmann, 1904, Hyalinobatrachium Ruiz-Carranza & Lynch, 1991, Hyalinobatrachium Ruiz-Carranza & Lynch, 1991, Hyalinobatrachium Ruiz-Carranza & Lynch, 1991, Hydrolaetare Gallardo, 1963, Hydrolaetere Gallardo, 1963, Hydrophylax Fitzinger, 1843, Hydrophylax L.f., Hydrophylax Matheson & Crosby, 1912, Hydrophyllax Raf., Hydatophylax Wallengren, 1891, Hydrophila Ehrh., Hydrophlox Jordan, 1878, Hydrophyga Lindholm, 1927, Hydrophysa Guenée, 1854, Hydrophila Ehrh. ex House, 1920, Hydrophylla Stackhouse, 1816, Habrophylax Meyrick, 1931, Hodophylax James, 1933, Hylophylax Ridgway, 1909, Hypophylax L.Fairmaire, 1904, Hylophylax Linnaeus, 1982, Hypophylax Townsend, 1935, Hydrophylax Fitzinger, 1843, Hydrophylax L.f., Hydrophylax Matheson & Crosby, 1912, Hydrophyllax Raf., Hydatophylax Wallengren, 1891, Hydrophila Ehrh., Hydrophlox Jordan, 1878, Hydrophyga Lindholm, 1927, Hydrophysa Guenée, 1854, Hydrophila Ehrh. ex House, 1920, Hydrophylla Stackhouse, 1816, Habrophylax Meyrick, 1931, Hodophylax James, 1933, Hylophylax Ridgway, 1909, Hypophylax L.Fairmaire, 1904, Hylophylax Linnaeus, 1982, Hypophylax Townsend, 1935, Hyla Laurenti, 1768)", "HasCoordinate is true", "HasGeospatialIssue is false", "Year is greater than or equal to 2000" ] } The dataset includes 109861 records from 745 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0011288-210914110416597/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences